2006
DOI: 10.1152/jn.00412.2006
|View full text |Cite
|
Sign up to set email alerts
|

Preparatory Gain Modulation of Visuomotor Transmission for Smooth Pursuit Eye Movements in Monkeys

Abstract: It has been reported that the visuomotor processing underlying the initiation of smooth pursuit eye movement is modulated in relation to the recent experience of eye movements: the initial pursuit eye velocity is larger after experiencing repeated pursuits than saccades. To assess which parameters of the previously executed pursuits play an essential role in modulating the gain of visuomotor transmission, we recorded the ocular responses of monkeys to a brief perturbing motion of the tracking target injected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
(66 reference statements)
0
13
1
Order By: Relevance
“…Therefore neural activity in the sites that store event history data might be maintained even during the ITI. On the other hand, we have reported that the preparatory gain increase in monkeys is triggered by the appearance of the tracking target (Tabata et al 2006). After the appearance of the target, the amplitude of the perturbation response gradually increases and reaches its peak 300 -600 ms after the target appearance (in the current study, the time between target appearance and onset of the perturbation was always 300 ms).…”
Section: Possible Neural Basis For Trial-by-trial Gain Modulationcontrasting
confidence: 47%
See 2 more Smart Citations
“…Therefore neural activity in the sites that store event history data might be maintained even during the ITI. On the other hand, we have reported that the preparatory gain increase in monkeys is triggered by the appearance of the tracking target (Tabata et al 2006). After the appearance of the target, the amplitude of the perturbation response gradually increases and reaches its peak 300 -600 ms after the target appearance (in the current study, the time between target appearance and onset of the perturbation was always 300 ms).…”
Section: Possible Neural Basis For Trial-by-trial Gain Modulationcontrasting
confidence: 47%
“…Thus the initial response to the target motion is principally governed by the visual properties such as eccentricity, velocity, and acceleration (e.g., Carl and Gellman 1987;Krauzlis and Lisberger 1994;Lisberger and Westbrook 1985;Lisberger et al 1981;Morris and Lisberger 1987;Tychsen and Lisberger 1986). Since the amplitude of the perturbation response is correlated with the magnitude of the initial pursuit response (Tabata et al , 2006, our results suggest that the initial pursuit response is not only generated by a transformation of the visual signal into motor command, but also influenced by an internal cognitive process that dynamically modulates the gain based on recent experiences.…”
Section: Possible Functional Role Of Preparatory Gain Modulation In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…A sudden change in target motion induces a corresponding perturbation response of eye motion (Churchland & Lisberger, 2002; Ono, 2013; Schwartz & Lisberger, 1994; Tabata et al, 2006). This approach evaluates how the visual input associated with a given speed and direction of image motion on the retina affects the on-line visual control in smooth pursuit eye movements.…”
Section: Introductionmentioning
confidence: 99%
“…The visuomotor gain associated with the initial pursuit is variable, which depends on ongoing behavioral states or cognitive factors (Barnes, 2008; Keating & Pierre, 1996; Krauzlis & Miles, 1996; Tabata, Miura, & Kawano, 2005; Tabata et al, 2006). For example, the initial pursuit response evoked by visual target motion is enhanced when the subjects anticipated the tracking of a moving target.…”
Section: Introductionmentioning
confidence: 99%